International Financial Statistics, July 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
This July 2015 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. This issue contains country pages for Marshall Islands, Palau, and Tuvalu. IFS contain country tables for most IMF members, as well as for Anguilla, Aruba, the Central African Economic and Monetary Community, Curacao, the currency union of Curacao and Sint Maarten, the Eastern Caribbean Currency Union, the euro area, Montserrat, the former Netherlands Antilles, Sint Maarten, the West African Economic Monetary Union, West Bank and Gaza, and some non-sovereign territorial entities for which statistics are provided internationally on a separate basis. Also, selected series are drawn from the country tables and published in area and world tables. The country tables normally include data on a country's exchange rates, IMF position, international liquidity, monetary statistics, interest rates, prices, production, labor, international transactions, government accounts, national accounts, and population. Selected series, including data on Fund accounts, international reserves, and international trade, are drawn from the country tables and published in world tables as well.